The Dielectric function of condensed systems - Keldysh, L. V., 1931-; Kirzhnits, D. A. (David Abramovich); Maradudin, Alexei A., 1931- (Modern problems in condensed matter sciences, 1989)
Much progress has been made in the understanding of the general properties of the dielectric function and in the calculation of this quantity for many classes of media. This volume gathers together the considerable information available and presents a detailed overview of the present status of the theory of electromagnetic response functions, whilst simultaneously covering a wide range of problems in its application to condensed matter physics. The following subjects are covered: - the dielectric function of the homogeneous electron gas, of crystalline systems, and of inhomogeneous matter; - electromagnetic fluctuations and molecular forces in condensed matter; - electrodynamics of superlattices.